Working through the ZOUD - Bailey, Catherine (Cranfield University School of Management, 2011)
Never has it been more necessary for management teams to be able to work through the Zone of Uncomfortable Debate (ZOUD) - that unspoken process that prevents us from questioning too closely the things that are held dear in business.